Modified murine intracranial aneurysm model: aneurysm formation and rupture by elastase and hypertension - Hosaka, Koji (BMJ Publishing Group, 2014)
INTRODUCTION: Cerebral aneurysms occur in up to 5% of the population. There are several murine models of aneurysms; however, all have limitations and none reproducibly model aneurysm rupture. To fulfill this need, we modified two current rodent aneurysm models to create a murine model which reproducibly produces intracranial aneurysms and rupture. METHODS: The left common carotid arteries and the right renal arteries were ligated in C57BL/6 female mice with a hypertensive diet. One week later, small burr holes were created with a stereotactic frame using the following stereotactic measurements: 1.2 mm rostral and 0.7 mm lateral to the right of the bregma. A 26 G needle was gradually advanced via the burr hole until contact with the skull base, upon which the needle was pulled back 0.3 mm. Five, 10 and 20 μL of 10 U/mL elastase solution and 10 μL of 1 U/mL elastase solution were stereotactically injected into the basal cisterns. Angiotensin II was then continually infused at a dose of 1000 ng/kg/min via an osmotic pump placed subcutaneously. In the control mice, 20 μL bromophenol blue solution was injected. Three weeks later, or earlier if mice expired prior to 3 weeks, the circle of Willis was inspected by microscopy for aneurysm formation and/or signs of rupture. Histological analyses were then performed to evaluate elastic lamina destruction, inflammatory cell and macrophage infiltration, absence of intimal endothelial cells and thickening of the smooth muscle layer within the aneurysm wall. To compare with human aneurysms, human aneurysm specimens (n=35; 34 unruptured and 1 ruptured) and normal control superficial temporal arteries (STAs) (n=9) were examined. RESULTS: All mice given 5, 10 and 20 μL of 10 U/mL elastase solution developed intracranial aneurysms within the circle of Willis; 40%, 60% and 50% of mice had ruptured aneurysms, respectively. In mice given 10 μL of 1.0 U/mL elastase solution, 90% developed intracranial aneurysms and 20% had ruptured aneurysms. Aneurysms were confirmed by examining the destruction of the elastic lamina. Aneurysms consistently demonstrated CD45 positive inflammatory cell and F4/80 positive macrophage infiltration within the aneurysm wall which was not present in the circle of Willis of normal sham-operated mice. These results were similar to those in human aneurysms and STA control arteries. CONCLUSIONS: We modified two current rodent aneurysm models to create a murine model that produces consistent aneurysms and rupture and can be used for studying cerebral aneurysm formation, rupture and treatment.